Gender Issues and Beyond:: intersectionality in DragArt - Costa Filho, Francisco Carlos; Silva Lopes, Elisabeth (Revista Brasileira de Estudos da Presença, 2024)
This article weaves together the analysis of contemporary studies and a brief repertoire of queer artists with identity issues and their intersectional relations. Through the notion of the body as a territory of political action, we examine how they have addressed, in creation, issues concerning identity, gender, sexuality, race, ethnicity, and class, which we consider to be urgent in terms of raising awareness and inciting political transformations inherent in antihegemonic artistic and pedagogical processes. Since one of the authors is a practitioner of drag queen, the body’s role in research matters. Nowadays, the recent category of drag queer and their associated subgenres enables us to engage in a dialogue with the concept of post-drag, as proposed by Luc Schicharin.